(untitled) (Indian Journal of Arid Horticulture, 2013)
Proper irrigation scheduling will help to assure efficient use of water and energy in crop production. To avoid wastage of water for crop irrigation it is necessary to develop methods that estimate plant water demands based on the needs to obtain good qualitative crop results. The quantity of irrigation water needed for fruit crops is greatly optimized under micro irrigation systems of different efficiencies. When using micro-sprinkler irrigation, 20% of irrigation water quantity can be conserved compared to surface irrigation, when using drip irrigation 33.3% and 16.6% of irrigation water quantity can be saved when compared to surface irrigation and sprinkler irrigation respectively. Studies were conducted on newly established Kinnow orchard under the arid conditions of Western Rajasthan in 2001. Both drip and microsprinkler systems th with differential water requirement dosages per irrigation scheduling were evaluated. The harvesting studies up to 5 year of production (2008) revealed that maximum average fruit weight, maximum fruit yield/tree and total yield was observed under 70% Crop evaporation as compared to 40% and 100% Crop evaporation treatments under both drip and micro-sprinkler system. The crop geometry studies on Kinnow plants under two planting densities (6x3m) and (6x6m) with respect to three th differential irrigation treatments (40%, 70% and 100% crop evapotranspiration) up to 8 year of bearing reveals that highest number of fruits/tree, maximum average fruit weight, maximum fruit yield/tree and total yield was observed under 100% Crop evaporation treatment under 6 x 3 m crop geometry of drip system whereas under traditional system (6 x 6 m) of Kinnow tree plantation, maximum average fruit weight, maximum fruit yield/tree and total yield was observed under 70% Crop evaporation treatments.